Fuzzy Ontology for Document Clustering Using Term Vector Techniques - Guptha, K Gurnadha; Vuna, Vidyasagar V; srinivas, A; Reddy, V.Nikesh Kumar (IJRDO -Journal of Computer Science Engineering, 2015)
The paper is a study on term Vector technique for Information Retrieval System. The resulting paper is the study of predefined multi-view fuzzy ontology over Distributed Document Clusters. The Term vector technique helps certain vies to solve problems faced in the current information retrieval systems. The paper addresses on in-effective use of a human time in analyzing and referencing to the names in a search expression. The resulting topic inherits lower level evidences like Cosine similarity, Term Weighting and arises to the new conceptual model called Term Vectors by repeated top-rank measures like TFIDF ( Term Frequency/ Inverse Document Frequency) measure, Awards in the field, Parsers and External links and Cross Lingual Information System by helping to bring a good text recognition in comparison. The test results in fair and reliable measures and enhances weighted accuracies.